Treatment of Libman-Sacks endocarditis by combination of warfarin and immunosuppressive therapy - Mehmet Rasih Sonsöz; Rukiye Dilara Tekin; Ahmet Gül; Zehra Buğra; Dursun Atılgan (KARE Publishing, 2019)
Antiphospholipid syndrome (APS) is a clinical disorder that creates an increased risk of arterial or venous thrombotic events or pregnancy-associated complications and includes the presence of autoantibodies against negatively charged phospholipids. This syndrome is often associated with systemic autoimmune diseases, such as systemic lupus erythematosus (SLE). Libman-Sacks endocarditis is a form of non-bacterial thrombotic endocarditis and is infrequently seen in APS. There are few data documenting the echocardiographic response of APS valve disease to medical treatment. This is an unusual case of a young female patient with SLE and APS who had chorea and non-bacterial thrombotic aortic valve endocarditis. Echocardiography revealed that the vegetation had receded after a combination of warfarin and immunosuppressive therapy.